2004
DOI: 10.1002/elsc.200400014
|View full text |Cite
|
Sign up to set email alerts
|

Growth on Phenol at Chemostress Levels Amplifies the Expression of the Phenol Degradation Pathway in Acinetobacter calcoaceticus

Abstract: Bacteria often use pollutants as sole carbon and energy sources. However, if they are toxic and the concentrations are high these compounds inhibit growth, and eventually poison the biocatalysts. In order to identify mechanisms contributing to stability, the protein patterns of Acinetobacter calcoaceticus during growth on potentially toxic phenol were analysed using two-dimensional gel electrophoresis. Enzymes involved in the catabolism or assimilation of phenol, such as phenol monooxygenase and catechol 1,2-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…CAT in a phenol-degrading strain of A. calcoaceticus plays a role in short-term adaptation of this strain to stress induced by phenol ( Benndorf et al, 2004 ). In CSY-P13 exposed to FA and PHBA, the activities of SOD, CAT, APX, and DHAR were elevated.…”
Section: Discussionmentioning
confidence: 99%
“…CAT in a phenol-degrading strain of A. calcoaceticus plays a role in short-term adaptation of this strain to stress induced by phenol ( Benndorf et al, 2004 ). In CSY-P13 exposed to FA and PHBA, the activities of SOD, CAT, APX, and DHAR were elevated.…”
Section: Discussionmentioning
confidence: 99%
“…This enables the cell to express the respective pathways only in the presence of an inducing substrate. In addition, proteome analysis has suggested that the induction of catabolic enzymes during growth on high concentrations of the potentially toxic organics as phenol could be a component of the response to chemostress in microorganisms which is able to metabolize these compounds [5]. This induction probably provides resistance against phenol poisoning by lowering the intracellular concentrations of phenol and catechol.…”
Section: Catechol 1 2-dioxygenase Activities During the Growth Of Amentioning
confidence: 98%
“…The reduction in biomass attributable to transfer alone is equated with the biomass reduction in the control vessels for the same phase in the experiment. For V 12 , the value of f t_12 is thus equated with f t_10 , which is determined from biomass reduction observed in the control vessels V 00 ! V 10 .…”
Section: Data Interpretationmentioning
confidence: 99%
“…Microorganisms that are effective at degrading pollutants can be stressed by exposure to these chemicals, as has been observed for Methylocystis sp. M and trichloroethylene [11], Acinetobacter calcoaceticus and phenol [12], Pseudomonas sp. B4 and polychlorinated biphenyls [13], and Pseudomonas putida KT2440 and toluene [14].…”
Section: Introductionmentioning
confidence: 99%